Teknik Pembelajaran Mufradat dalam Perspektif Teori Belajar Edward Lee Thorndike - Ahmadi, Maswan (AL-WARAQAH Jurnal Pendidikan Bahasa Arab, 2023)
Mufradat learning occupies an important place in starting an Arabic language learning process. Mufradat is like a provision towards mastering language skills because it will be used to form written and spoken sentences to communicate. Thorndike's theory is an alternative to Mufradat learning. He mentioned three laws of learning, namely, the Law of Readiness, the Law of Exercise and the Law of Effect. By using this, a Mufradat learning technique emerges which is quite good if followed at every stage. Starting from learning preparation, learning process, and evaluation of Mufradat learning.